
化简:(1)﹣3x 2 y+2x 2 y+3xy 2 ﹣2xy 2 ;(2)3(a 2 ﹣2ab)﹣2(﹣3ab+b 2 );(3)5abc﹣{2a 2
化简:(1)﹣3x2y+2x2y+3xy2﹣2xy2;(2)3(a2﹣2ab)﹣2(﹣3ab+b2);(3)5abc﹣{2a2b﹣[3abc﹣(4a2b﹣ab2]}....
化简:(1)﹣3x 2 y+2x 2 y+3xy 2 ﹣2xy 2 ;(2)3(a 2 ﹣2ab)﹣2(﹣3ab+b 2 );(3)5abc﹣{2a 2 b﹣[3abc﹣(4a 2 b﹣ab 2 ]}.
展开
展开全部
解:(1)原式=(﹣3+2)x 2 y+(3﹣2)xy 2 =﹣x 2 y+xy 2 ; (2)原式=3a 2 ﹣6ab+6ab﹣2b 2 =3a 2 ﹣2b 2 ; (3)原式=5abc﹣[2a 2 b﹣(3abc﹣4a 2 b+ab 2 )] =5abc﹣(2a 2 b﹣3abc+4a 2 b﹣ab 2 ) =5abc﹣2a 2 b+3abc﹣4a 2 b+ab 2 =8abc﹣6a 2 b+ab 2 . |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询